Business customers segmentation with the use of K-means and self-organizing maps : an exploratory study in the case of a Slovenian bank - Simic, Slavisa (2016)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Information Systems and Technologies Management